University presses in libraries: potential for successful marriages. Issue 3 (5th August 2014) - Missingham, Roxanne; Kanellopoulos, Lorena
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss the role of libraries and university presses and to present the Australian National University (ANU) Press and Library as a case study of successful structural integration. Design/methodology/approach – The paper analyses current debates about libraries as structural centres for running university presses. Taking into consideration the major areas of debate, the methodology used is to analyse the operation of the press; compare the financial parameters to two traditional Australian university presses; analyse the policy and procedures of the press; review the benefits to the university, library and press of the current operation; and outline issues for the future. Findings – Over the past 10 years, the ANU Press has developed into a major producer of open access scholarly outputs. The relationship with the Library has enabled a sharing of information, joint work on issues such as access and copyright and a platform from which integrated support for scholarly communication can occur. Research limitations/implications – The article is a detailed case study of the ANU Press. Further studies could compare the operations of other university presses that are located within universities and analyse the fit of different models. Practical implications – The model used at ANU has been used to develop two other presses in Australia, with some modifications. It can be used by other universities. Originality/value – Establishing libraries as the structural home for university presses is an area of hotly contested debate. This is a systematic review of a model of a press located within a library. It has resulted in both internal cooperation within the scholarly communication paradigm and a research impact of approximately one million downloads a year. It provides insights into the role of libraries in scholarly communication that have been the basis of assertions in current debate, providing information that will support further experimentation and more informed discussions.